Strategic interaction vs. regulatory compliance among regulated utilities: The Swedish water sector - Erik Lundin (Research Institute of Industrial Economics (IFN), 2013)
This study provides the first empirical test of strategic interactions in the pricing decisions of regulated utilities. Since publicly owned water utilities in Sweden are governed by a cost-of-service regulation, prices in neighboring municipalities should not affect the own price other than through spatially correlated cost factors. In contrast, spatial dependence is pronounced. This behavior can be explained in terms of an informal yardstick competition: When consumers use neighboring utilities' prices as benchmarks for costs or as behaviorally based reference prices, utilities will face the risk of consumer complaints and successive regulatory reviews if deviating too much from neighbors' prices.
Keywords: D4; L1; L5; L9; 330; yardstick competition; spatial econometrics; public economics; utilities